Pengeringan Jagung Bertongkol Pada Saat Cuaca Tidak Bersahabat - Tamrin, Tamrin; Kuncoro, Sapto; Novita, Dwi Dian (abe.fp.unila.ac.id, 2024)
The introduction of the paper should explain the nature of the problem, previous work, purpose, and the contribution of the paper. The abstract should summarize the content of the paper. Try to keep the abstract below 250 words. Do not make references nor display equations in the abstract. The journal will be printed from the same-sized copy prepared by you. Your manuscript should be printed on A4 paper (21.0 cm x 29.7 cm). The margins and style described below should be adhered to carefully. This will enable us to keep uniformity in the final printed copies of the Journal. Please keep in mind that the manuscript you prepare will be photographed and printed as it is received. Readability of copy is of paramount importance. Keywords: Drying, Corn on the Cob, Crops in the Field, Plastic, The Greenhouse Effect.